Design of a cadaver rotation system - Garman, Kevin; Boudreaux, Chloe; Ezell, Jack; Mahoney, Phillip (Kansas State University. K-State Libraries, 2015)
The Kansas State University (KSU) Cadaver Dissection Team (CDT) is challenged to provide comprehensive human anatomy demonstrations to regular lab students. However, to see all structures adequately, the cadaver must be flipped over. Attempting to rotate a 300-pound cadaver without proper aid may result in labor injury, cadaver tissue damage, compromised lab spaces, and lost preservatives. The Rotational Anatomy Senior Design team is creating a system to help the CDT lift and rotate their cadavers. This design project was broken into two categories: harness and lift. The harness interfaces with the cadavers, while the lift is the supporting structure connecting to the harness and instigating rotational movement. After designing multiple frameworks for the lift, the team ran numerous Finite Element Analysis (FEA) models representing a concentrated static force slightly larger than that produced by the maximum cadaver weight via SolidWorks Simulation. This showed that the lift designed was able to withstand the weight of a 330-pound cadaver with minimal to no flexion. Rotational Anatomy also created a harness that distributes the cadaver's weight by wrapping around the legs and continuing up the shoulders, keeping the cadaver both stable and horizontal during lift and rotation. Upon installing the electric winch system, the lift and harness designs will be thoroughly tested with CDT's current cadavers and volunteer design team members. The criteria for successful testing are: 1) less than 1/16" flexion for framework means it is safe and stable and 2) no tears or ripped seams on harness means it is durable and appropriate. Time permitting, the framework will undergo polishing touches: rubber trimming to mitigate wall damage, and a powder coating to deter rust after years of use. Upon timely and successful test results, both the lift and the harness will be implemented in the Cadaver Dissection Lab by May 2015.
Citation: Garman, K., Boudreaux, C., Ezell, J., & Mahoney P. (2015). Design of a cadaver rotation system. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Group category, grand prize
Keywords: Rotation of cadavers; Biomedical engineering design work